Penerapan Pendekatan Kontekstual Pada Mata Pelajaran Bahasa Indonesia Materi Majas Untuk Siswa Kelas 6 Sekolah Dasar - Suprihatien Suprihatien; Lailatul Hasanah; Maulana Rafi Rulis Saputra; Feri Hermawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is a lifelong process that encompasses all human learning experiences, thus requiring a learning approach that aligns with the times and the needs of learners. The Merdeka Curriculum emerges as a policy that provides schools with the freedom to create meaningful, enjoyable, and learner-centered learning. In the Indonesian language subject, particularly in the material on figurative language, it was found that sixth-grade elementary school students have difficulty understanding the types and meanings of figurative language due to the dominance of lecture methods and the limited concrete learning media. This study uses a descriptive qualitative method supplemented with pre-tests and post-tests to analyze the effectiveness of the contextual approach (Contextual Teaching and Learning/CTL) in improving student understanding. The results of the study show a significant increase in learning outcomes, marked by an increase in the number of students achieving the completeness of 5 students in the pre-test became 16 students in the post-test, as well as an increase in the average score from 48.70 to 71.48. These findings indicate that the contextual approach is able to help students relate the concept of figures of speech to real experiences, increase active engagement, and strengthen interpretative abilities. Thus, CTL has been proven effective in improving Indonesian learning outcomes on the subject of figures of speech in the sixth grade of elementary school.